Clinical Outcomes of Meniscal Allograft Transplantation With Respect to the Minimal Clinically Important Difference. Issue 12 (October 2022) - Su, Lisa; Garcia-Mansilla, Ignacio; Kelley, Benjamin; Arshi, Armin; Fabricant, Peter D.; Sherman, Seth L.; Jones, Kristofer J.
Background: Arthroscopic-assisted meniscal allograft transplantation (MAT) has become a viable and effective treatment option for young active patients with postmeniscectomy pain. The minimal clinically important difference (MCID) of patient-reported outcome measures (PROMs) is imperative to evaluate the clinical significance of surgical interventions and inform clinical practice guidelines in orthopaedic surgery. Purpose: To perform a systematic review of clinical outcome studies of patients undergoing MAT and compare postoperative improvement with established MCID thresholds. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: A systematic review was performed using the PubMed, Web of Science, and Cochrane Library databases. A meta-analysis was performed using data obtained from studies reporting patient-reported outcomes. Subgroup analysis was performed on patients undergoing isolated lateral MAT using fresh-frozen grafts. Weighted mean postoperative improvements in the International Knee Documentation Committee (IKDC), Lysholm, and visual analog scale for pain (VAS pain) were calculated and compared with MCID values to determine if they met the MCID threshold. Results: A total of 35 studies were identified, including 1658 unique patients. Weighted mean postoperative score improvements exceeded MCID thresholds for the VAS pain, IKDC, and Lysholm. Subgroup analysis of patients undergoing isolated lateral fresh-frozen MAT demonstrated postoperative improvements exceeding the MCID for the Lysholm and VAS pain. Conclusion: Evaluating postoperative PROMs with respect to the MCID is crucial to evaluate the effect of MAT on functional improvement. The results of the present meta-analysis suggest that postoperative improvements after MAT are clinically meaningful as reflected by PROMs exceeding the MCID threshold for the IKDC, Lysholm, and VAS pain.